2013
DOI: 10.1021/am302938a
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Quantum-Dot-Doped Polypyrrole Counter Electrode for High-Performance Dye-Sensitized Solar Cells

Abstract: Herein graphene quantum dot (GQD), a graphene material with lateral dimension less than 100 nm, is explored to dope PPy on F-doped tin oxide glass as an efficient counter electrode for high-performance dye-sensitized solar cells (DSSCs). The GQDs-doped PPy film has a porous structure in comparison to the densely structured plain PPy, and displays higher catalytic current density and lower charge transfer resistance than the latter toward I3(-)/I(-) redox reaction. The highest power conversion efficiency (5.27%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(80 citation statements)
references
References 40 publications
4
76
0
Order By: Relevance
“…However, Pt is a noble metal with high expense and low storage, which will extensively limit the mass production and practical application of DSSCs. With this information, various materi- [20] firstly used graphene quantum dots (GQDs) to dope polypyrrole (PPY), where GQDs-doped PPY as CE for DSSCs achieved a power conversion efficiency (PCE) of 5.27%, being superior to that of PPY (4.46%). Such an idea would be a promising and efficient strategy to further extend and boost the electrochemical performance of CoS-derived CE material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Pt is a noble metal with high expense and low storage, which will extensively limit the mass production and practical application of DSSCs. With this information, various materi- [20] firstly used graphene quantum dots (GQDs) to dope polypyrrole (PPY), where GQDs-doped PPY as CE for DSSCs achieved a power conversion efficiency (PCE) of 5.27%, being superior to that of PPY (4.46%). Such an idea would be a promising and efficient strategy to further extend and boost the electrochemical performance of CoS-derived CE material.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon quantum dots (CQDs), nano-sized carbon particles, have attracted growing interest due to their high photochemical stability, low toxicity, good biocompatibility, and low environmental impact [18,19]. It has also been demonstrated that CQDs are of great potential in energy storage and conversions [20][21][22]. It is well known that there are abundant negative charged oxygen-containing functional groups on the surface of CQDs.…”
mentioning
confidence: 99%
“…Hence, their huge potential for memory devices [13], supercapacitors [14], fuel cells [15], photovoltaic devices [16,17], light-emitting diodes [18] was revealed. Furthermore, different architectures of solar cells based on GQDs have been proposed, where they form heterojunctions with crystalline silicon or silicon nanowires [19,20] and organic bulk heterojunction [21] on one hand, or they were embedded in polymers to replace the standard TiO 2 photoanode [22] or Pt counter electrode [23] in DSSCs on the other hand. In ultraviolet spectral range, GQDs have extinction coefficients ranging from 10 to 200·10 3 M -1 cm -1 [24], larger than that of common fluorophores, and comparable to those of semiconductor quantum dots (QDs) [25].…”
Section: Introductionmentioning
confidence: 99%
“…As well known, lattice defects such as defective sites at the edges of graphene are considered as main electrocatalytic active sites for the reduction of I 3 À [40,41]. Based on the fact that the edge planes of the graphene exhibit faster electron-transfer kinetics than the basal planes and the high D/G ratio exists in the shells of CNTs, the optimized hybrid CNTs/graphene with defectrich edge planes has great potential as the catalytic material for the reduction of I 3 À to be applied in DSSCs [10,42].…”
Section: Resultsmentioning
confidence: 99%